SIKAP, NORMA SUBJEKTIF, DAN INTENSI PEGAWAI NEGERI SIPIL UNTUK MENGADUKAN PELANGGARAN (WHISTLE-BLOWING) - Suryono, Erwan; Chariri, Anis (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This study aims to investigate factors that influence civil servants to whistle-blow fraud. It also investigates the effect of government’s bureaucracy reforming program on the civil servants’ intention to whistle-blow fraud. By employing the theory of reasoned action, this study included variables of subjective norms, attitudes, and whistle-blowing intentions. This study used primary data gathered from questionnaires of 293 respondents. Respondents were civil servants in the ministries/agencies that have and have not implemented bureaucratic reforms. The findings of this study indicated that subjective norms positively affected the attitudes and intentions of civil servants to report the wrongdoings. However, the attitudes had no significant effect on civil servants’ whistle-blowing intentions. In addition, there are no significant differences on subjective norms, attitudes, and whistle-blowing intentions between civil servants in ministries/agencies that have implemented bureaucratic reforms and civil servants in ministries/agencies that have not implement bureaucratic reforms.